VARIASI KESULITAN SISWA DALAM MENYELESAIKAN MASALAH KONTEKSTUAL BERDASARKAN TEORI POLYA - Junianti, Ika Wulan; Subanji; Susanto, Hery (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2025)
Contextual problem-solving ability is a crucial skill that students, particularly those in vocational schools, must possess, as they will immediately enter the workforce. To optimize students' abilities, research was conducted on the variation of students’ difficulties in solving problems. This study aims to identify variations in vocational high school students' difficulties in solving contextual problems of the system of linear inequalities in two variables based on Polya’s theory and to offer alternative solutions that can be used to overcome these difficulties. The type of research used is qualitative with a descriptive approach. The study subjects were 3 students of 36 students of the grade XI vocational high school, who had received the material. These students were selected based on the category of abilities they had, namely high, medium, and low, as well as considerations of communication of teacher recommendation results. Data collection was carried out through tests and interviews. Based on the results of the study, it was found that 1) Low Ability Students (LAS) experienced many variation in difficulties at all stages in solving problems according to Polya’s theory, 2) Medium Ability Students (MAS) at the stage of understanding the problem experienced fewer variations in difficulties compared to the other three stages, 3) High Ability Students (HAS) at the stage of understanding the problem and making plans experienced fewer variation in difficulties compared to the other two stages. Apart from being based on Polya’s theory, students also experience other variations of difficulty, namely the difficulty in defining variables, constants, and coefficients correctly. Abstrak: Kemampuan penyelesaian masalah kontekstual adalah kemampuan penting yang harus dimiliki oleh siswa khususnya siswa sekolah kejuruan karena mereka akan langsung terjun ke dunia kerja. Untuk mengoptimalkan kemampuan siswa maka dilakukan penelitian terkait variasi kesulitan siswa dalam menyelesaikan masalah kontekstual. Penelitian ini bertujuan untuk mengidentifikasi variasi kesulitan siswa SMK dalam menyelesaikan masalah kontekstual sistem pertidaksamaan linear dua variabel berdasarkan teori Polya dan menawarkan solusi alternatif yang bisa digunakan untuk mengatasi kesulitan tersebut. Jenis penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Subjek penelitian sebanyak tiga siswa dari 36 siswa kelas XI SMK yang telah mendapatkan materi tersebut. Siswa ini dipilih berdasarkan kategori kemampuan yang dimiliki yaitu tinggi, sedang, dan rendah serta pertimbangan komunikasi hasil rekomendasi guru. Pengumpulan data dilakukan melalui tes dan wawancara. Berdasarkan hasil penelitian didapatkan bahwa: 1) Siswa Kemampuan Rendah (LAS) mengalami banyak variasi kesulitan pada seluruh tahapan dalam penyelesaian masalah menurut teori Polya; 2) Siswa Kemampuan Sedang (MAS) pada tahapan memahami masalah mengalami variasi kesulitan lebih sedikit dibandingkan dengan tiga tahap lainnya; 3) Siswa Kemampuan Tinggi (HAS) pada tahapan memahami masalah dan membuat rencana mengalami variasi kesulitan lebih sedikit dibandingkan dua tahapan lainnya. Selain berdasarkan teori Polya, variasi kesulitan lainnya yaitu kesulitan untuk mendefinisikan variabel, konstanta, dan koefisien secara tepat juga dialami oleh siswa.